2013
DOI: 10.7150/ijms.7292
|View full text |Cite
|
Sign up to set email alerts
|

High-expression of DJ-1 and Loss of PTEN Associated with Tumor Metastasis and Correlated with Poor Prognosis of Gastric Carcinoma

Abstract: Background and aims: DJ-1 and PTEN have been shown to involve in multiple cell processes and play an important role in cancer development and progression. However, their relationship with gastric carcinoma (GC) has not been identified yet. The purpose of this study is to clarify the relationship of DJ-1 and phosphatase and tensin homolog (PTEN) with clinicopathological parameters and prognosis in GC.Methods: 114 specimens were collected from GC patients and expression of DJ-1 and PTEN in tissue microarray was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…These studies indicated that reduction or absence of PTEN expression is a dynamic process during the course of gastric cancer progression, and that PTEN levels can be used as an indicator to diagnose the pathological state of gastric cancer. Other studies exploring the role and mechanism of action of PTEN in gastric cancer, found similar results Bai et al, 2013;Li et al, 2013).…”
Section: Roles Of Pten In Gastric Cancersupporting
confidence: 66%
“…These studies indicated that reduction or absence of PTEN expression is a dynamic process during the course of gastric cancer progression, and that PTEN levels can be used as an indicator to diagnose the pathological state of gastric cancer. Other studies exploring the role and mechanism of action of PTEN in gastric cancer, found similar results Bai et al, 2013;Li et al, 2013).…”
Section: Roles Of Pten In Gastric Cancersupporting
confidence: 66%
“…It has been well established that PTEN may serve functions in a number of biological processes, including cell proliferation, the cell cycle, apoptosis, migration, invasion, metastasis, metabolism, differentiation, transcription and translation through negative regulation of the PI3K/AKT signaling pathway (38)(39)(40)(41)(42). Li et al (24) reported that in gastric cancer, PTEN expression is low in tumor tissues and was associated with advanced clinical stage and poor prognosis of patients with gastric cancer. Zheng et al (43) identified that decreased PTEN expression was significantly associated with depth of invasion, lymphatic invasion, lymph node metastasis, liver metastasis and Union Internationale Contre le Cancer staging of gastric cancer (44).…”
Section: Discussionmentioning
confidence: 99%
“…3A). A low expression of PTEN was previously demonstrated that in gastric cancer tissues, and PTEN expression was associated with the formation and progression of gastric cancer (24)(25)(26)(27). A luciferase reporter assay was performed to evaluate whether PTEN is a direct target gene of miR-136.…”
Section: Mir-136 Directly Targets and Regulates Pten Expression In Gamentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN), a key negative regulator of the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway, is also a direct target of miR-106b (13). One previous study had reported that PTEN served as a tumor-suppressing gene in cancer invasion and metastasis (14). Additionally, PTEN is a key factor in inducing EMT (15).…”
Section: Introductionmentioning
confidence: 99%